Occurrence of aac(6’)-Ib-cr and Qnr Genes among Quinolone-Resistance Enterobacteriaceae Isolated from Patients with Urinary Tract Infection in Najaf, Iraq - MH. Al-Hilali, Samer A.; A.Hussein, Ahmed; Edrees Shubb, Ebtehal; Obaid Khza, Alaa Mahdy; Majeed, Mohauman (IIUM Medical Journal Malaysia, 2025)
INTRODUCTION: The aac(6’)-Ib-cr gene is one of the most common genes among plasmids and has dual activity against both aminoglycoside and quinolone antibiotics, making it among the most important plasmid-mediated quinolone resistance genes. This research aimed to confirm the frequency of aac(6’)-Ib-cr and qnr genes in quinolone-resistant Enterobacteriaceae isolates obtained from patients with urinary tract infection in Najaf, Iraq. MATERIALS AND METHODS: Quinolone resistance was examined in 318 urine samples taken from individuals who had suspected urinary tract infections (135 Klebsiella pneumonia cases, 75 Proteus mirabilis cases, and 108 Escherichia coli cases). Using PCR, antibiotic susceptibility patterns were assessed for quinolone resistance isolates and the presence of the aac(6’)-Ib-cr, qnrA, qnrB, and qnrS were looked into. RESULTS: Quinolone-resistant isolates totaling 176 were identified. aac(6’)-Ib-cr was detected in 93 (52.8%) cases, 50 of which were E. coli, 39 were K. pneumonia, and 4 were P. mirabilis, according to PCR analysis data. qnrA 6 (3.4%), qnrB 22 (12.5%), and qnrS 5 (2.8%) isolates were identified to have the following qnr genes. P. mirabilis did not have the qnrS gene, which was absent from all analyzed genes detected in bacterial isolates. CONCLUSION: It was shown that of the plasmid-mediated quinolone resistance genes, the aac(6’)-Ib-cr gene was the most common. Every gene analyzed was present in both K. pneumoniae and E. coli.